Diagnostic accuracy of multi-detector row computed tomography and magnetic resonance imaging in assessment of mandibular involvement, cervical lymph node metastases and T parameter staging of squamous cell carcinomas of tongue and floor of mouth - Kumar, Ravinder; Jaiswal, Gagan; Kundu, Jyoti (Journal of Kathmandu Medical College, 2017)
Background: Tongue and floor malignancies can be diagnosed based on biopsy and clinical examination, but diagnostic imaging is essential to confirm and define the size and extent of the disease. Objectives: The aim of this study was to recognise and understand the extent and precision of the diagnostic accuracy of multi-detector row computed tomography (MDCT) and magnetic resonance imaging (MRI) in mandibular tumour involvement, cervical lymph node metastases, T staging of tongue and floor of mouth malignancies in order to represent the proper treatment plan. Methods: Fifty patients with histologically proven squamous cell carcinomas (SCC) of tongue and floor of mouth malignancies underwent both multi-detector row computed tomography and magnetic resonance imaging before surgery. Two radiologists independently, unaware of the findings, in consensus reviewed and interpreted all images to determine the extent of the primary tumour (T), mandibular tumour invasion and cervical lymph node metastasis. Imaging results obtained were correlated with postoperative histopathologic findings that represented our referencestandard. Cohen’s kappa index and McNemar test were used to verify the concordance between the two radiologists and above mentioned three study parameters. Results: Magnetic resonance imaging showed superiority to multi-detector row computed tomography in the evaluation of the T parameter staging of TNM classifi cation and medullary bone involvement while multi-detector row computed tomography was more accurate compared to magnetic resonance imaging in the visualization of small cortical bone erosions. However, both the modalities demonstrated similar diagnostic performance in detection of metastatic lymph nodes. Conclusion: Multi-detector row computed tomography and magnetic resonance imaging have nearly equal potential for detecting the tumour size, mandibular infiltration and nodal metastases. Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, page:104-111